Colon Crypts of Subjects With Familial Adenomatous Polyposis Show an Increased Number of LGR5+ Ectopic Stem Cells. Issue 5 (17th May 2021) - Jennelle, Lucas T.; Dampier, Christopher H.; Tring, Stephanie; Powell, Steven; Casey, Graham
Abstract : INTRODUCTION: Familial adenomatous polyposis (FAP) is a hereditary colorectal cancer (CRC) syndrome characterized by accelerated adenoma development due to inherited (or de novo ) mutations in the APC regulator of WNT signaling pathway ( APC ) gene. The mechanism underlying this accelerated polyp development in subjects with FAP has not been defined. Given that LGR5+ stem cells drive crypt cell proliferation, we hypothesized that FAP crypts would demonstrate aberrant leucine-rich repeat–containing G-protein–coupled receptor 5 (LGR5) staining patterns. METHODS: Biopsies were taken from 11 healthy subjects, 7 subjects with Lynch syndrome, 4 subjects with FAP, and 1 subject with MUTYH -associated polyposis syndrome during routine screening or surveillance colonoscopy. Crypt staining was evaluated by immunohistochemistry of paraffin-embedded tissue sections. Stem cell numbers were estimated by immunofluorescence staining of isolated crypts using antibodies against LGR5 and other proteins. RESULTS: Subjects with FAP exhibited a greater number of LGR5+ stem cells in their crypts than healthy subjects and subjects with Lynch syndrome and MUTYH -associated polyposis syndrome. Most crypts of subjects with FAP harbored LGR5+ cells located above the lower third of the crypts. DISCUSSION: These findings support a model in which inactivation of one copy of APC leads to increased numbers of LGR5+ stem cells, many of which are ectopic, in colon crypts of subjects with FAP. Overabundant and ectopic LGR5+ stem cells could lead to an expanded proliferative zone of dividing cells more likely to develop mutations that would contribute to the accelerated adenoma development observed in FAP.